Guidance on the Utilization of Artificial Intelligence (AI) in the Development of Instructional Materials - Risma Firda Diana; Pratama Surya Bagus Kusuma; Husnu Athoilah; Choirun Nisa (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Using AI in primary education can enhance teachers’ efficiency in developing instructional materials aligned with the Merdeka Curriculum, reduce their workload, and improve the quality of learning through contextual and continuous training. This activity was conducted at Madrasah Ibtidaiyah Swasta Darul Ulum Lamongan due to its diverse student population, strong commitment to improving educational quality, and the pressing need to develop technological innovations in the teaching and learning process in the region. The method involved tutorials, hands-on practice, and discussions carried out in three phases: needs assessment, intensive training with mentoring, and evaluation through reflection and feedback. Results indicate that the AI-assisted learning management support program was successfully implemented and received positive responses from participating teachers. The process began with a needs analysis through discussions and surveys, revealing low levels of digital literacy and limited experience among teachers using AI tools. The core training phase was delivered through tutorials and practical sessions using applications like ChatGPT and Merlin AI to help design teaching materials. Interactive discussions encouraged active participation and boosted teachers’ confidence. The final evaluation showed that teachers felt significantly supported, became more efficient in performing administrative tasks, and were motivated to integrate AI into their teaching activities sustainably. Conclusion: The integration of artificial intelligence through tutorials, practical sessions, and discussions effectively enhanced teachers’ ability to design innovative and efficient instructional materials, while also promoting the integration of technology into the learning process.